Hedonism Lifestyle in College Students Uin K.H Abdurrahman Wahid Pekalongan - Hikmahtian Nurnafilah; Hendri Hermawan Adinugraha; M. Shulthoni (Journal of Noesantara Islamic Studies, 2024)
The development of technology and modernization has led to changes in values and lifestyles among university students. They tend to be more contemporary in dress, food, drink and communication. The rise of modern shopping centers such as malls, cafes, and coffee shops isalso well received by students, most of whom come from the upper middle class. This indicates the tendency of hedonistic lifestyle among students, which is influenced by internal factors such as personality and external factors such as social class and group. The purpose of this study is to explain the description of hedonism lifestyle in college students and the factors of hedonism lifestyle in college students. The subjects of this research are students of UIN K.H Abdurrahman Wahid Pekalongan who like to hang out or have fun at cafes, restaurants, and others. This research uses a qualitative approach and is described in descriptive form. The datacollection technique used in this research is interview. Data analysis is done by grouping into categories and describing the data obtained according to the category. The results showed thathedonism lifestyle among students of UIN K.H. Abdurrahman Wahid Pekalongan is reflectedin the tendency of high interest in seeking and prioritizing pleasure. The factors behind it, bothinternal such as personality and external such as social class, especially social class, are dominant factors. The hedonistic lifestyle has a significant impact on students' academic aspects, such as procrastination, decreased achievement, and inactivity in lectures. Students' perceptions regarding the hedonism lifestyle also vary, some consider it important but some view it as not the main need.